"It's Important, but It's Not Everything": Practitioners' Use, Analysis and Perceptions of Fitness Testing in Academy Rugby League - Sam McCormack; Ben Jones; Sean Scantlebury; Dave Rotheram; Kevin Till (MDPI AG, 2020)
A plethora of research exists examining the physical qualities of rugby league players. However, no research has investigated practitioners' insights into the use, analysis and perceptions of such fitness testing data that is vital for applying research into practice. Therefore, this study aimed to examine practitioners' (coaches and strength & conditioning [S&C] coaches) perceptions and challenges of using fitness testing and the development of physical qualities. Twenty-four rugby league practitioners were purposefully sampled and completed a semi-structured interview. Interviews were transcribed and thematically analysed identifying five themes (it's important, but it's not everything; monitoring; evaluation and decision making; motivation; and other external challenges). The theme of "it's important, but it's not everything" emerged as a fundamental issue with regard fitness testing and the use of such data and that physical data alone does not inform coaches decisions. There appears conflicts between coaches and S&C coaches' perceptions and use of fitness data, identifying complexities of supporting players in multidisciplinary teams. Collectively, the findings highlight the multifaceted nature of academy rugby league and suggest that practitioners should utilise fitness testing to inform player evaluations, positively influence training and assist with decision making. Moreover, practitioners should understand the combination of factors that influence fitness testing and work collaboratively to enhance talent development strategies.